A study on loss and gain in meaning in the english translations of cognitive metaphors expressing the notion of “self” in trinh cong son‟s songs - Lê Thị Oanh (2015)
In light of Cognitive Linguistics, metaphor is an important tool not only in language use but also in human conceptual system. Thanks to cognitive metaphors, we know the way people view and function the world through abstract concepts they live by. “Self” is an elusive concept, and commonly viewed and expressed in terms of cognitive metaphors. This study attempts to conduct a research into cognitive metaphors denoting the concept of “Self” in Trinh Cong Son (TCS)‟s songs as manifested in their English translations. Cognitive metaphors of the notion of “Self” in TCS‟s songs will be explored based on the theoretical background of cognitive semantics and data collected from questionnaire and interviews. Besides, it also finds out loss and gain in the English translations of these cognitive metaphors of “Self” for better understanding of cognitive metaphors of “Self” in TCS‟s songs. The results show that cognitive metaphors of “Self” in Trinh Cong Son‟s songs are rooted in bodily experiences and in experiences with culture and physical world. Furthemore, results gained through loss and gain in the English translations indicate that loss and gain in such translations in terms of semantics and syntax are mostly inevitable due to the influence of the sound beats in the STs, the linguistic and cultural discrepancies between English and Vietnamese. Loss is also caused by trategies employed by the translators such as using a more neutral/less expressive words, meronymy, unrelated words and phrases. Misunderstanding the author‟s ideas is also a contributory factor for such loss. Loss is more prevalent than gain in the English translations. Gain, on the other hand, is mostly realized through expansions or explainations. Finally, the study is expected to be benificial in areas such as English language teaching and learning, translation studies of songs and cross-cultural communication.